2018
DOI: 10.1177/2470547018786390
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar and Prefrontal Cortical Alterations in PTSD: Structural and Functional Evidence

Abstract: Background: Neuroimaging studies have revealed that disturbances in network organization of key brain regions may underlie cognitive and emotional dysfunction in posttraumatic stress disorder (PTSD). Examining both brain structure and function in the same population may further our understanding of network alterations in PTSD. Methods: We used tensor-based morphometry (TBM) and intrinsic connectivity distribution (ICD) to identify regions of altered volume and functional connectivity in unmedicated individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 58 publications
11
52
0
1
Order By: Relevance
“…Finally, accumulating evidence repeatedly demonstrates functional and structural abnormalities in the cerebellum of PTSD patients (34)(35)(36)(37)(38)(39). Moreover, two recent studies have shown reduced functional nodal strength in the cerebellum in PTSD (19,40). In the current study, PTSD patients continued to show reduction in cerebellar connectivity posttreatment compared to controls (Fig.…”
Section: Figure 3 the Effects Of Psychotherapy On Executive Connectisupporting
confidence: 68%
“…Finally, accumulating evidence repeatedly demonstrates functional and structural abnormalities in the cerebellum of PTSD patients (34)(35)(36)(37)(38)(39). Moreover, two recent studies have shown reduced functional nodal strength in the cerebellum in PTSD (19,40). In the current study, PTSD patients continued to show reduction in cerebellar connectivity posttreatment compared to controls (Fig.…”
Section: Figure 3 the Effects Of Psychotherapy On Executive Connectisupporting
confidence: 68%
“…While the cerebellum has long been viewed as a unit of motor control, it is becoming increasingly apparent that the cerebellum, especially the neocerebellum (posterior lobe) that is mainly connected to the cerebral cortex, plays important roles in emotion and cognition (44). Recent work by Holmes and colleagues also found reduced nodal strength in the cerebellum of PTSD patients, as well as reduced volume and structural covariance (45). Other studies have also reported structural and functional abnormalities in the cerebellum in PTSD (46)(47)(48)(49)(50)(51).…”
Section: Figure 4 Effect Of Symptom Provocation On Salience Global Cmentioning
confidence: 99%
“…zaburzeniami postrzegania własnego ciała (Sakson-Obada 2009), ale też problemami kardiologicznymi (Remch i in. 2018), zmianami o charakterze neurologicznym (Holmes 2018).…”
Section: Kontekst Społecznyunclassified